Readiness Reporting for an Adaptive Army - Pernin, Christopher G. (RAND Corporation, 2013)
This study examines the readiness reporting system in light of changes experienced by Army units in the past decade, a period in which the Army learned to adapt to emerging requirements by adding new capabilities quickly and flexibly. The current readiness reporting system captures only a portion of those changes in capabilities and has some important limitations. The study recommends ways to improve the reporting system for an adaptive Army.